Inhibitory effects of Ginkgo biloba extract on vascular endothelial growth factor in rat aortic endothelial cells. - ZHANG Li; RUI Yao-Cheng; YANG Peng-Yuan; QIU Yan; LI Tie-Jun; LIU Hou-Chun (Acta Pharmacologica Sinica, 2016)
AIM: To study the protective effects of Ginkgo biloba extract (GbE) against rat aortic endothelial cells (RAEC) damage induced by lysophosphatidylcholine (LPC). METHODS: Cell injury were determined by MTT assay and LDH release. Vascular endothelial growth factor (VEGF) protein production from RAEC was determined by enzyme-linked immunosorbent assay (ELISA). VEGF mRNA expression was examined by in situ hybridization and dot blot. RESULTS: GbE 0.01-1 microg/L prevented LPC-induced injury in cultured RAEC in a concentration-dependent manner. Cultured RAEC could express VEGF protein and VEGF mRNA was induced by LPC 5 mg/L. GbE could inhibit the expression of VEGF protein and VEGF mRNA in co-cultured RAEC with LPC. CONCLUSION: LPC could induce a strong expression of VEGF in RAEC. GbE could protect RAEC against the LPC-induced damage and downregulate VEGF protein and VEGF mRNA expression in cultured RAEC.